MENGURANGI PERILAKU HIPERAKTIF PADA ANAK AUTIS MELALUI PERMAINAN TRADISIONAL EGRANG DI SLB NEGERI KOTA PARIAMAN (Single Subject Research Pada Anak Autis di Kelas III C) - Setia Komala Sari (Universitas Negeri Padang, 2014)
This research was aimed at revealing whether the traditional game Egrang could make the hyperactive students stay on seat for 30 minutes. This research was conducted at SLB Negeri Kota Pariaman. This was an experimental research which used Single Subject Research (SSR). In conducting the research, A-B design was applied. The result of the research revealed that in the baseline condition (A) the hyperactive behavior of the child was varied from thevb first to the fourth day, and it remained the same on the fifth to the seventh day. At the end of the baseline phase, the student was able to stay on seat for 4 minutes and it improved into 13 minutes at the end of the intervension condition. Furthermore, the overlapping of data in this research was 0%, indicating that the intervension given significantly affect the changes over the child’s behavior. Thus, it was concluded that the use of traditional game egrang could decrease the hyperactive behavior of student especially on willingness to stay on seat.